Design and syntheses of ortho-, meta- and paraxylylguanidinium-Zn²⁺- cyclen complexes and their interactions with DNA / Nor Amin Hassan - Hassan, Nor Amin (2018)
Three new zinc ions (Zn²⁺) complexes, C¹, C² and Cᶟ, were designed and synthesized by coordination of Zn²⁺into the integrated 1,4,7,10-tetraazacyclododecane (cyclen) and ortho-, meta- and para-bromoxylylguanidinium pendants group. A retrosynthetic analysis was carried out to identify and solve problems with regard the selection of organic reactions. The syntheses were performed in five steps including of (i) Gabriel and Ing-Manske primary amine synthesis, (ii) SN2 substitution reaction, (iii) guanylation of primary amine, (iv) deprotection of Boc group, and (v) coordination of Zn²⁺ complex. All the Zn²⁺ complexes structures were characterized by 1H- and 13CNMR spectroscopy, infrared spectroscopy and mass spectrometry. The aim of synthesizing these Zn²⁺ complexes was to confirm the anticipated interactions of Zn²⁺ complexes towards natural DNA as well as to explore the phosphatase activity of such complexes. Hence, ethidium bromide (EB) fluorescence assay and circular dichroism (CD) spectroscopy were used to ascertain the interaction between Zn²⁺ complexes towards natural DNA i.e. calf thymus (ctDNA). The former assay demonstrated a displacement of EB from its complexes with ctDNA, thus confirming the affinity of these Zn²⁺ complexes towards DNA. CD spectroscopic results also revealed that C¹ has disturbed both base stacking and right handed helicity properties of ctDNA, but retained the B-form of its structure. By contrast, C2 and C3 transformed the conformation of ctDNA from B-form into Z-form. This was further supported by thermal denaturation studies showing ATm values of C¹, C², and Cᶟ to be +2, +4 and +5, respectively. The catalytic properties of these complexes for phosphate hydrolysis was evaluated using phosphodiesters bis(p-nitrophenyl)phosphate (BNPP) as a model and monitoring by UV spectrometry. The BNPP hydrolysis results {ca. 17% after 8 days incubation) suggested that C¹, C², and Cᶟ were endowed with still modest yet significant catalytic properties.